Role of Laser Etching on Shear Bond Strength between Recast Nickel-Chromium Alloy and Dental Ceramic: An Experimental Study - Janardanan Sriman; Ahila Singaravel Chidembaranathan; Muthukumar Balasubramanium (Frontiers in Dentistry)
Objectives: The purpose of this study was to investigate the effect of laser etching, air bone particle abrasion and acid etching on shear bond strength between re-cast Nickel Chromium alloy and dental ceramics.